The Effect Of Brand Sensory Experience On Brand Loyalty With The Mediation Of Brand Attitude And Brand-Self Connection On Tokopedia - Omar Davala; Erlita Ridanasti (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the effect of sensory brand experience on brand loyalty on the Tokopedia e-commerce platform by involving Brand Attitude and Brand-Self Connection as mediating variables. This study uses a quantitative approach with primary data collection through questionnaires analyzed using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. The results of the study indicate that sensory brand experience has a significant positive effect on brand loyalty, with Brand Attitude acting as a mediator that strengthens the relationship. Conversely, Brand-Self Connection does not provide a significant mediating effect, so further research is needed. The implications of this study emphasize the importance of sensory experience-based strategies to increase customer loyalty, as well as the need for an approach that supports consumer emotional connectedness.